Advances in Natural Multimodal Dialogue Systems - van Kuppevelt, Jan; Dybkjær, Laila; Bernsen, Niels Ole (Text, Speech and Language Technology, 2005)
References 74 Part II Annotation and Analysis of Multimodal Data: Speech and Gesture 4 FORM 79 Craig H. Martell 1. Introduction 79 2. Structure of FORM 80 3. Annotation Graphs 85 4. Annotation Example 86 5. Preliminary Inter-Annotator Agreement Results 88 6. Conclusion: Applications to HLT and HCI? 90 Appendix: Other Tools, Schemes and Methods of Gesture Analysis 91 References 95 5 97 On the Relationships among Speech, Gestures, and Object Manipulation in Virtual Environments: Initial Evidence Andrea Corradini and Philip R. Cohen 1. Introduction 97 2. Study 99 3. Data Analysis 101 4. Results 103 5. Discussion 106 6. Related Work 106 7. Future Work 108 8. Conclusions 108 Appendix: Questionnaire MYST III - EXILE 110 References 111 6 113 Analysing Multimodal Communication Patrick G. T. Healey, Marcus Colman and Mike Thirlwell 1. Introduction 113 2. Breakdown and Repair 117 3. Analysing Communicative Co-ordination 125 4. Discussion 126 References 127 7 131 Do Oral Messages Help Visual Search? Noëlle Carbonell and Suzanne Kieffer 1. Context and Motivation 131 2. Methodology and Experimental Set-Up 134 3. Results: Presentation and Discussion 141 4. Conclusion 153 References 154 Contents vii 8 159 Geometric and Statistical Approaches to Audiovisual Segmentation Trevor Darrell, John W. Fisher III, Kevin W. Wilson, and Michael R. Siracusa 1. Introduction 159 2. Related Work 160 3. Multimodal Multisensor Domain 162 4. Results 166 5. Single Multimodal Sensor Domain 167 6.